Optical, Electrical, and Electromechanical Properties of Hybrid Graphene/Carbon Nanotube Films. (11th April 2015) - Kholmanov, Iskandar N.; Magnuson, Carl W.; Piner, Richard; Kim, Jin‐Young; Aliev, Ali E.; Tan, Cheng; Kim, Tae Young; Zakhidov, Anvar A.; Sberveglieri, Giorgio; Baughman, Ray H.; Ruoff, Rodney S.
Abstract : By combining a graphene layer and aligned multiwalled carbon nanotube (MWNT) sheets in two different configurations, i) graphene on the top of MWNTs and ii) MWNTs on the top of the graphene, it is demonstrated that optical, electrical, and electromechanical properties of the resulting hybrid films depend on configurations.